Analysis of financial time series - Tsay, Ruey S. (Hoboken, N.J. : Wiley, 2005)
Provides a comprehensive and systematic introduction to financial econometric models and their applications in modeling and predicting financial time series data. This latest edition continues to emphasize empirical financial data and focuses on real-world examples.
"Wiley-Interscience."
Includes bibliographical references and index.
oif 26/10/15
Loan
Keywords: Time-series analysis; Econometrics; Risk management